Potential therapeutic effects of GS-441524 and GC376 in cats with feline infectious peritonitis - Nekouei, Omid; St-Hilaire, Sophie; Hui, Pak Chun; Chan, Karen; Chan, Isabel Sumyi; Ngan, Sum Yuet Lorraine; Chan, Yion; Chung, Ka Po; Hong, Sunguk; Chan, Hiu Man; et al. (Veterinary Evidence, 2022)
PICO question In cats with feline infectious peritonitis (FIP), does treatment with the nucleoside analogue GS-441524 or the protease inhibitor GC376, compared to supportive measures alone, lead to longer survival times? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Five studies, including four uncontrolled interventional studies and one case-series were critically reviewed Strength of evidence Moderate Outcomes reported The reviewed studies collectively provide moderate evidence in support of the application of GS-441524 or GC376 to extend the survival time of cats suffering from feline infectious peritonitis Conclusion While these antiviral drugs are considered the most likely options for FIP treatment, more robust evidence should be obtained through well-designed randomised controlled trials to verify the observed positive effects in treating various forms of the disease and the potential long-term side effects. However, the ethical dilemmas of conducting double blinded placebo-controlled trials, which by necessity include untreated cats with an invariably fatal disease are recognised How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.